Frequency and Predictors of Internal Mammary Artery Graft Failure and Subsequent Clinical Outcomes: Insights From the Project of Ex-vivo Vein Graft Engineering via Transfection (PREVENT) IV Trial. Issue 2 (12th January 2016) - Harskamp, Ralf E.; Alexander, John H.; Ferguson, T. Bruce; Hager, Rebecca; Mack, Michael J.; Englum, Brian; Wojdyla, Daniel; Schulte, Phillip J.; Kouchoukos, Nicholas T.; de Winter, Robbert J.; Gibson, C. Michael; Peterson, Eric D.; et al.
Abstract : Background—: The internal mammary artery (IMA) is the preferred conduit for bypassing the left anterior descending (LAD) artery in patients undergoing coronary artery bypass grafting. Systematic evaluation of the frequency and predictors of IMA failure and long-term outcomes is lacking. Methods and Results—: The Project of Ex-vivo Vein Graft Engineering via Transfection (PREVENT) IV trial participants who underwent IMA-LAD revascularization and had 12- to 18-month angiographic follow-up (n=1539) were included. Logistic regression with fast false selection rate methods was used to identify characteristics associated with IMA failure (≥75% stenosis). The relationship between IMA failure and long-term outcomes, including death, myocardial infarction, and repeat revascularization, was assessed with Cox regression. IMA failure occurred in 132 participants (8.6%). Predictors of IMA graft failure were LAD stenosis <75% (odds ratio, 1.76; 95% confidence interval, 1.19–2.59), additional bypass graft to diagonal branch (odds ratio, 1.92; 95% confidence interval, 1.33–2.76), and not having diabetes mellitus (odds ratio, 1.82; 95% confidence interval, 1.20–2.78). LAD stenosis and additional diagonal graft remained predictive of IMA failure in an alternative model that included angiographic failure or death before angiography as the outcome. IMA failure was associated with a significantly higher incidence of subsequent acute (<14 days of angiography) clinical events, mostly as a result of a higher rate of repeat revascularization. Conclusions—: IMA failure was common and associated with higher rates of repeat revascularization, and patients with intermediate LAD stenosis or with an additional bypass graft to the diagonal branch had increased risk for IMA failure. These findings raise concerns about competitive flow and the benefit of coronary artery bypass grafting in intermediate LAD stenosis without functional evidence of ischemia. Clinical Trial Registration—: URL:http:/www.clinicaltrials.gov . Unique identifier: NCT00042081. Abstract : Supplemental Digital Content is available in the text.